2011
DOI: 10.1371/journal.pone.0028345
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Beriberi among African Union Troops in Mogadishu, Somalia

Abstract: Context and ObjectivesIn July 2009, WHO and partners were notified of a large outbreak of unknown illness, including deaths, among African Union (AU) soldiers in Mogadishu. Illnesses were characterized by peripheral edema, dyspnea, palpitations, and fever. Our objectives were to determine the cause of the outbreak, and to design and recommend control strategies.Design, Setting, and ParticipantsThe illness was defined as acute onset of lower limb edema, with dyspnea, chest pain, palpitations, nausea, vomiting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…This implies that vitamin B 1 deficiency affects the contents of other B-group vitamins. The vitamin B 1 deficiency beriberi occurs even in recent years in poor countries that consume rice as their staple food 413. Vitamin B 1 deficiency manifests with a severe decrease in appetite, decrease in growth, and peripheral neurologic symptoms of paresthesias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that vitamin B 1 deficiency affects the contents of other B-group vitamins. The vitamin B 1 deficiency beriberi occurs even in recent years in poor countries that consume rice as their staple food 413. Vitamin B 1 deficiency manifests with a severe decrease in appetite, decrease in growth, and peripheral neurologic symptoms of paresthesias.…”
Section: Discussionmentioning
confidence: 99%
“…All of these reported that thiamin therapy produced complete, rapid clinical recovery in all cases. One paper stated: “the patient was administered intramuscular thiamin and this resulted in rapid and dramatic improvement of his condition within hours, including resolution of edema and cardiac symptoms.”13 These reports imply that the vitamin B 1 deficiency would not affect the other B-group vitamins, including vitamin B 12 413. We could not find papers examining the influence of vitamin B 1 -deficiency on the contents of other B-group vitamins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemics of beriberi manifesting with sensory neuropathy and gait ataxia have been described in children and adults within segments of the African population subsisting on diets that provide marginal or submarginal intakes of thiamine in prison populations and in garrisoned troops …”
Section: Thiamine Deficiency Disorders In Children and Adultsmentioning
confidence: 99%
“…142 Plasma albumin and globulin levels in wet beriberi are normal. [143][144][145] there is increased cardiac output despite a depression of left ventricular function; plasma renin, angiotensin II and aldosterone levels are lower than in patients with low output heart failure. 146 Although thiamine deficiency occurs much more frequently in malnourished children than in controls, Hailemariam et al could not relate this to the occurrence of oedema in malnutrition.…”
Section: Idiopathic Oedemamentioning
confidence: 99%